2009
DOI: 10.1044/1092-4388(2009/07-0167)
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acoustic and Kinematic Approaches to Measuring Utterance-Level Speech Variability

Abstract: Purpose-The spatio-temporal index (STI) is one measure of variability. As currently implemented, kinematic data are used, requiring equipment that cannot be used with some patient groups or in scanners. An experiment is reported that addressed whether STI can be extended to an audio measure of sound pressure of the speech envelope over time, that did not need specialized equipment.Method-STI indices of variability were obtained from lip track (L-STI) and amplitude envelope (E-STI) signals. These measures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…Variability, assessed by the STI, decreased throughout the acquisition phase. Finally, Howell et al (2009) showed a moderate but significant correlation between the STI for lip movements and the rectified and integrated audio signal for the same utterance.…”
Section: Introductionmentioning
confidence: 91%
“…Variability, assessed by the STI, decreased throughout the acquisition phase. Finally, Howell et al (2009) showed a moderate but significant correlation between the STI for lip movements and the rectified and integrated audio signal for the same utterance.…”
Section: Introductionmentioning
confidence: 91%
“…Participant numbers in previous studies have therefore been low, impacting on the statistical power and predictions made by these experiments. In order to address these problems, methods involving acoustic data collection and analysis have been successfully validated in replicating findings of the kinematic STI (Howell, Anderson, Bartrip, & Bailey, 2009). Acoustic recordings are a well established method of data collection in speech disorders and allow capturing of performance from a large number and wider variety of speakers.…”
Section: Introductionmentioning
confidence: 99%
“…At the level of acoustic inconsistency, measures such as the acoustic spatiotemporal variability indices (e.g., envelope-based spatiotemporal index [E-STI]; Howell, Anderson, Bartrip, & Bailey, 2009) or voice onset time (VOT) variability (Iuzzini-Seigel, 2012) have clinical potential for differential diagnosis and treatment progress monitoring in CAS, but they have rarely been applied in this population. Generally, children's VOTs are more variable than adults' VOTs, and variability decreases with age and stabilizes around the age of 11 years (Auzou et al, 2000;Whiteside, Dobbin, & Henry, 2003).…”
Section: Error Inconsistency In Casmentioning
confidence: 99%
“…Acoustic Spatiotemporal Variability Indices Assessment of speech variability via audio signals is clinically feasible even in difficult-to-test populations and has been recently proposed by several researchers (Anderson, Lowit, & Howell, 2008;Cummins, Lowit, & van Brenk, 2014;Howell et al, 2009; see Table 5). The acoustic STI is calculated in a similar manner to its kinematic variant but from the amplitude envelope derived from rectified and low-pass filtered speech audio recordings (Howell et al, 2009). As the source signal for variability calculation is the amplitude envelope, Howell et al (2009) refer to this as E-STI.…”
Section: Acoustic Measuresmentioning
confidence: 99%
See 1 more Smart Citation